University Teaching and the Ethics of Care: A Reflection in Relation to the Experience of COVID-19 (Theological Kronos, 2021)
In the face of the crisis caused by the Covid-19 pandemic, the need to rethink the teaching practice in the fields of Higher Education (HE) has resurfaced. The social and human crisis related to social isolation due to mandatory lockdown, the concern for one’s own health or that of others and the loss of lives has highlighted the need to adopt a more humane conception of teaching that enables a closer accompaniment between teachers and students. During this reflection, from the author’s teaching experience and the proposal of the Brazilianphilosopher and theologian Leonardo Boff, we present how the ethics of care applied to the field of university teaching can respond, at least partially, to the challenges posed by the search of a quality HE fully aware of human fragility. Also of mental health care and the transformations caused by the pandemic. One of the most important: the integration of face-to-face and virtual education strategies.
Keywords: University teaching; Higher education; Ethics of care; Caring attitude; mental health; Psyco-spirituality; online education; University; Pandemic; Covid-19